Baroness von Hellman’s Dark Personality Gillespie’s Cruella (2021) - Shalicha, Awalia Nur; Santoso, Heri Dwi; Nugraheni, Yunita (Universitas Stikubank (UNISBANK) Semarang, 2024)
The film Cruella is a comedy-crime film directed by Craig Gillespie in 2021. This film tells the story of a beautiful and creative woman named Estella who dreams of becoming a designer. On a circuitous journey, Estella met a famous designer of that time named Baroness von Hellman. They eventually achieved very good cooperation, until it reached a point where they were enemies with each other. The focus of this research is Baroness von Hellman's personality as the antagonist in the film. Researchers are interested in studying the representation of Baroness von Hellman's dark personality and how this personality can dominate her. This research uses the dark triad personality theory to examine Baroness von Hellman's actions which represent her dark personality. In the dark triad of personality, there are three categories of behavior that reflect a dark personality, namely Machiavellianism, narcissism, and psychopathy. The research method used is descriptive qualitative with data sourced from the film Cruella. The results of this research are that Baroness von Hellman's dark triad personality type which has the strongest influence is narcissism. This personality encourages acts of Machiavellianism and psychopathy to fulfill his obsessions. Meanwhile, the factors that cause a dark personality to be more dominant include physical, intelligence, family social strata, and environment. Keywords: Machiavellianism, narcissism, psychopathy, personality development